Implementasi Metode 4R untuk Peningkatan Literasi Lingkungan Menuju Sekolah Berkelanjutan - Novika Adi Wibowo; Alfyananda Kurnia Putra; Waode Yunia Silviariza; Mochammad Tri Herwanto; Aura Julita Andiansyah; Annisa Anna Firdausi; Dedy Zain Mochtar Asri; A Riyan Rahman Hakiki; Chyta Anindhyta (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2025)
Waste is an environmental problem that has an impact on environmental pollution. The implementation of waste management needs to be applied in the world of education. Teachers and students need to be involved through efforts to increase environmental literacy to realize sustainable schools with the 4R method. The purpose of community service is the implementation of the 4R method in waste management to increase environmental literacy to realize sustainable schools. The method used is Participatory Action Research (PAR). Community service activities regarding waste management are divided into three activities. The first activity is socialization regarding waste management in schools. The second activity is giving quizzes and environmental practices. The third activity is evaluation and follow-up in the form of measuring environmental literacy. The results of environmental literacy show medium and high categories based on indicators of environmental knowledge (64.10% is included in the high category), cognitive ability (61.54% is included in the medium category), environmental behavioral ability (64.10% is included in the medium category) and attitudes towards the environment (69.23 is included in the high category). The conclusion of the community service shows the importance of strengthening environmental literacy through the implementation of the 4R method that is fun and effective.